PENGARUH STRES KERJA DAN PERILAKU CYBERLOAFING TERHADAP KINERJA KARYAWAN - Puspita, Advensia Yesie Riani; Sudiro, Achmad (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to analyze the effect of job stress and cyberloafing industry on the performance of Kawi Branch Office of Bank Rakyat Indonesia in Malang. This explanatory research explains the relationship between variables. Using saturated sampling, 82 members of the population were selected as the sample. The data was harvested from Likert-scaled questionnaires and was analyzed using multiple linear regression and descriptive statistics analysis in IBM SPSS Statistics version 26. This study finds that (1) job stress and cyberloafing influence employee performance, (2) job stress affects employee performance, and (3) cyberloafing behavior influences employee performance. Therefore, this research suggests organizations to consider the balance between work load and time limit for employees and to make regulations regarding the use of computer and internet belonging to the organizations in order to enhance employee performance.